CAPITALIZATION OF COMPANIES: THEORETICAL ASPECT - Zaitseva, Lyudmyla (Socio-economic relations in the digital society, 2020)
The company’s capitalization is the most important financial indicator, which reflects the results of operations and future prospects for generating a flow of income by stock market participants. The purpose of the article is to substantiate the theoretical foundations of company capitalization and the influence of factors on the formation of company value.The article reveals the essence and main characteristics of capitalization, demonstrates the relationship between capitalization and the value of the company. Based on the analysis of definitions, process, cost, resource, analytical, system, process-effective, cognitive approaches to the study of company capitalization are distinguished. Options for increasing the value of companies are presented. It is substantiated that the capitalization process is a multifaceted and dynamic phenomenon, the result of purposeful creation and management of the value of companies. Emphasis is placed on the need to manage the capitalization process of the company, to increase value due to the positive dynamics of financial indicators. It is proved that the level of capitalization of companies depends on many factors: general and specific; microeconomic, which relate to a particular enterprise and macroeconomic, which are determined by the external conditions of the world, national economy and the situation in the field of specialized specialization of the company; basic, strategic and operational factors that allow you to structure groups of factors according to their priority according to the specific financial and economic situation. In the hierarchy of priorities for the appropriate structuring of factors influencing capitalization, the following groups are identified: 1) basic factors of capitalization — inherent in the company, regardless of the scenarios of its development; 2) strategic factors of capitalization — priority for the activities of companies to achieve strategic goals; 3) operational / speculative capitalization factors — factors that allow to achieve a high level of capitalization in the shortest possible time. The mechanism of influence of macroeconomic factors on the capitalization of companies is characterized. Emphasis is placed on the need to develop a system of priority factors in accordance with the situational approach, taking into account the conditions of specific market opportunities and threats.
Keywords: capitalization of companies; capital; value of companies; macroeconomic factors; microeconomic factors; system of priority of factors